Optimization of the Condition of Palm Frond Torrefaction Process by Utilizing Liquid Torrefaction Product as Pre-treatment for Improve Product Quality - Wenny Susanty; Zuchra Helwani; Bahruddin Bahruddin (Jurnal Rekayasa Kimia & Lingkungan, 2019)
Abstract